Heidelberg Risk Sport-Specific Stress Test: a paradigm to investigate the risk sport-specific psycho-physiological arousal - Frenkel, Marie Ottilie; Laborde, Sylvain; Rummel, Jan; Voigt, Laura; Kasperk, Christian; Plessner, Henning; Heck, Robin-Bastian; Strahler, Jana (Frontiers in psychology, 2019)
In risk sports with medium to high risks of injury (e.g., surfing, free solo climbing, wingsuit flying), athletes frequently find themselves in unexpected and threatening situations. Elevated psycho-physiological stress responses to these situations might have tremendous consequences for their performance as well as for their long-term health. To gain a better understanding of the psycho-physiological response to such events, innovative, externally valid and standardized stress induction protocols are needed. Therefore, the aim of this paper is to introduce and evaluate a risk sport-specific stress protocol, i.e., Heidelberg Risk Sport-Specific Stress Test (HRSST), which utilizes fear of falling as the stressful event. Climbing novices were asked to climb up a 12 meters high wall. Then, participants were requested to “jump into the rope” leading to a secured fall of about 3 m. This imposed physical danger assumed to elicit psycho-physiological responses. Self-reported state anxiety, salivary cortisol, and heart rate/heart rate variability were measured before, during, and after the HRSST. Results of four independent studies that investigated the psycho-physiological response to the HRSST in 214 participants were analyzed, leading to conclusions about the stressor’s effectiveness. Results showed that self-reported state anxiety consistently increased after the HRSST in all four experiments (moderate to large effects). The results of the physiological indicators were inconclusive. Salivary cortisol significantly increased after the HRSST in two of four experiments (large effect sizes). Although heart rate significantly increased during the “jump in the rope” in experiment 1, heart rate variability significantly decreased after the HRSST in only one of three experiments (small effect sizes). Findings suggest that the HRSST is a valid method to induce risk sport-specific emotional stress, but effects on physiological stress markers were rather minor. To sum up, in case of appropriate sports climbing facilities, the HRSST appears to be a cost-efficient and promising stress induction protocol: It offers the possibility to investigate risk sport specific stress responses and its underlying mechanisms in climbing novices. These findings may also find application in professions in which individuals are exposed to risky situations, such as police officers, medical first responders, firefighters and military personnel.